Analisis Hubungan Beban Kerja dan Stres Kerja pada Karyawan Logistik: Peran Work-Life Balance sebagai Mediator di PT. Wahana Lintas Nusantara - Karimah, Nurul; Nitte, Eka Putri Prinanda; Mujanah, Siti; Fianto, Achmad Yanu Alif (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the relationship between workload and job stress among logistics employees at PT. Wahana Lintas Nusantara, highlighting the role of work-life balance as a mediator. In the logistics industry, high workloads often lead to job stress, which negatively impacts employee well-being and company productivity. This research involved 120 operational employees as respondents, who completed questionnaires related to workload, job stress, and work-life balance. Path analysis was employed to identify both direct and indirect relationships among the variables. The findings reveal that workload has a significant positive effect on job stress, indicating that the higher the workload experienced by employees, the greater the level of stress they feel. However, work-life balance plays a significant mediating role, where a balanced work and personal life can mitigate the negative impact of workload on job stress. These findings suggest that company efforts to support work-life balance, such as flexible work schedules, adequate leave, and mental health programs, can help employees manage stress and enhance their well-being. This study provides valuable insights for the management of PT. Wahana Lintas Nusantara in designing policies that promote work-life balance for employees. Furthermore, it contributes to the academic literature on the relationship between workload, job stress, and work-life balance in the logistics sector, particularly in Indonesia.